2018
DOI: 10.1021/acs.nanolett.8b01007
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Structural Evolution and Anomalous Mechanical Response of Nanoglasses by Cryogenic Thermal Cycling

Abstract: One of the central themes in the amorphous materials research is to understand the nanoscale structural responses to mechanical and thermal agitations, the decoding of which is expected to provide new insights into the complex amorphous structural-property relationship. For common metallic glasses, their inherent atomic structural inhomogeneities can be rejuvenated and amplified by cryogenic thermal cycling, thus can be decoded from their responses to mechanical and thermal agitations. Here, we reported an ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…4, the fraction volume of loose packing structures for S1, S2 and S3 is 9.9%, 12.9% and 13.4%, respectively. Previous works showed that the fraction volume of loose structure for conventional metallic glasses is in the range of 20-25%, which is much higher than our results [35,36]. It is suggested that when an element is dominant in the atomic structure and several minor added elements are in the chemical compositions, the disordering phenomenon can be intensified in the microstructure.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…4, the fraction volume of loose packing structures for S1, S2 and S3 is 9.9%, 12.9% and 13.4%, respectively. Previous works showed that the fraction volume of loose structure for conventional metallic glasses is in the range of 20-25%, which is much higher than our results [35,36]. It is suggested that when an element is dominant in the atomic structure and several minor added elements are in the chemical compositions, the disordering phenomenon can be intensified in the microstructure.…”
Section: Resultscontrasting
confidence: 79%
“…P 0 is the loading rate, t c defines the relaxation time and, G 1 and G 2 introduce the modulus of dense-and loose-packing structures, respectively. Fitting the mentioned equation and the load-displacement curve, it is possible to attain G 1 and G 2 data and subsequently, the volume fraction of loose packing structures can be achieved as follows [35]:…”
Section: Resultsmentioning
confidence: 99%
“…(2)- (5). The data given in ref [32] and n depends on the grain morphology and pore geometry of the material and is determined to n & 3 [25], indicating that pores are interconnected. We assume a & 1 thus implying that ordered packing of pores is absent [28,29].…”
Section: 1mentioning
confidence: 94%
“…Cryogenics, a branch of physics that could cause intriguing changes in the properties of matter, play an important role in aerospace, biological engineering, infrared detectors, and energy technology, such as cryogenics can reduce the thermal noise to obtain reliable signals, decrease the reaction rate to capture the details of the reaction process in chemical research, and can be used for the simulation requirements of space exploration equipment. These fields require precise control of the appropriate temperature to meet different application requirements, where the cryogenic sensor is a fundamental measurement that can accurately reflect temperature changes in cryogenic environments. Conventional cryogenic thermometer generally require physical contact and thermal transmission, which are not suitable in many situations due to the limitation of spatial resolution, sensitivity and accuracy of detection . Efforts based on upconversion (UC) luminescence can provide a noncontact temperature measurement method, exhibiting fast response speed, high spatial resolution, and wide measurement range, which could provide the possibility for designing reliable cryogenic sensors owing to the diversification thermal response mechanisms of rare earth ions.…”
Section: Introductionmentioning
confidence: 99%